687.141.017.872.004.12 ANALYSIS OF MECHANICAL PROPERTIES OF HIGH ELASTIC KNITTED FABRICS FOR SPORTSWEAR DESIGN: Compression sportswear - Monnopov, Joxongir; Kayumov, Jurabek; MAKSUDOV, Nabijon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article considers the most important factors in the analysis of modern assortments of materials with compression properties. For the design of compression sports garments, fabric samples were selected, their mechanical properties were analyzed, and experimental test results were conducted using standard methods. To evaluate the compressive strength of fabrics, it was tested on the YG026T equipment. The YG026A-Ⅲ brand equipment was used to determine the deformation characteristics. The elasticity of the experimental samples was studied and the elongation diagram of the results of the evaluation of the one-cycle deformation characteristics is presented.